Cancer Pain: Part 1: Pathophysiology; Oncological, Pharmacological, and Psychological Treatments: A Perspective from the British Pain Society Endorsed by the UK Association of Palliative Medicine and the Royal College of General Practitioners - Jon H. Raphael; Sam H. Ahmedzai; Joan Hester; Catherine Urch; Janette Barrie; John E. Williams; Paul Farquhar-Smith; Marie Fallon; Peter Hoskin; Karen Robb; Mike Bennett; Rebecca Haines; et al. (2010)
Objective. This discussion document about the management of cancer pain is written from the pain specialists' perspective in order to provoke thought and interest in a multimodal approach to the management of cancer pain, not just towards the end of life, but pain at diagnosis, as a consequence of cancer therapies, and in cancer survivors. It relates the science of pain to the clinical setting and explains the role of psychological, physical, interventional and complementary therapies in cancer pain. Methods. This document has been produced by a consensus group of relevant health care professionals in the United Kingdom and patients' representatives making reference to the current body of evidence relating to cancer pain. In the first of two parts, pathophysiology, oncological, pharmacological, and psychological treatment are considered. Conclusions. It is recognized that the World Health Organization (WHO) analgesic ladder, while providing relief of cancer pain towards the end of life for many sufferers worldwide, may have limitations in the context of longer survival and increasing disease complexity. To complement this, it is suggested that a more comprehensive model of managing cancer pain is needed that is mechanism-based and multimodal, using combination therapies including interventions where appropriate, tailored to the needs of an individual, with the aim to optimize pain relief with minimization of adverse effects.